THE IMPACT OF BRAND TRUST TOWARD LOYALITY CUSTOMER PERTALITE IN DEPO PERTAMINA MOJOKERTO - Poernomo, Tri Tjahjo (Research In Management and Accounting (RIMA), 2020)
This study aims to analyze the effect of the viability (dov) and imtentonality (doi) dimensions on customer loyalty. The research sample consisted of 43 permanent pertalite participants who made repeat purchases at DEPO PERTAMINA Prajurit Kulon, Mojokerto, through the accidental sampling method approach (Cooper & Emory, 1995). It is concluded that H1 of research: the truth is accepted, H2 of research: the truth is accepted. Where loyalty is a manifestation of the moral it is positive shown by consumers to their retailers, in line with the opinion (Autry et al. 2007). The research model is quite accurate in predicting the linear influence of brand trust (dov & doi) on customer loyalty, representing 43 permanent participants who made intention purchases.